IPOs – not so much money on the table. The cost compensation hypothesis. - Zaremba, Adam; Kamiński, Karol (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
One of the most extensively documented anomalies concerning initial public offerings is IPO underpricing. Although the phenomenon is well analyzed and explained, most of the research ignores an individual investor's costs, constraints and perspective. We suppose that after taking these issues into consideration, there may be not much money left on the table. The paper consists of three main parts. First, we characterize IPO underpricing anomaly and review the performance patterns from many countries together with their theoretical explanations. In the second section, we indicate the usually ignored issues which may potentially significantly impede IPO investments. The last part of the paper presents the empirical analysis based on 209 offerings in the Polish stock market between 2001 and 2010. The paper comes to the conclusion that high IPO returns result from just a few outliers and are not significantly higher than the benchmark returns. As we have hypothesized, IPO underpricing seems to be just a compensation for costs and time constraints faced by investors
Argumenta Oeconomica, 2011, Nr 1 (26), s. 149-176
Keywords: post-IPO performance; Polish stock market; underpricing; long-term underperformance; hot issue markets; pierwsza oferta publiczna; giełda; rynek akcji